Biodegradation of PHBV/GNS nanocomposites by Penicillium funiculosum - Stieven Montagna, Larissa; Amaral Montanheiro, Thaís Larissa do; Chiodi Borges, Aline [UNESP]; Yumi Koga-Ito, Cristiane [UNESP]; Paula Lemes, Ana; Cerqueira Rezende, Mirabel (Wiley, 2017)
Biodegradable polymer nanocomposites are an essential alternative to minimize the generation of polymeric solid waste that shows short shelf life and difficult degradation. In this study, nanocomposites based on poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) were prepared by the incorporation of different contents, 0.25, 0.50, 0.75, and 1.00 wt % of graphite nanosheets (GNS), using a solution casting method. The investigation of the PHBV samples biodegradation was made using filamentous fungi (Penicillium funiculosum) in solid medium. Characterization of the material was performed by weight loss, differential scanning calorimetry, carbonyl index determined by Fourier transformed infrared spectroscopy, contact angle, roughness, and scanning electron microscopy. Results revealed that PHBV/GNS nanocomposites can be totally degraded in the presence of Penicillium funiculosum; however, it will be necessary high incubation period. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2017, 134, 44234.
Keywords: biodegradable; biopolymers & renewable polymers; nanoparticles; nanowires and nanocrystals; polyesters